Multitargeting Effects of Calebin A on Malignancy of CRC Cells in Multicellular Tumor Microenvironment - Buhrmann, Constanze; Kunnumakkara, Ajaikumar B.; Kumar, Aviral; Samec, Marek; Kubatka, Peter; Aggarwal, Bharat B.; Shakibaei, Mehdi (Frontiers in Oncology, 2021)
Background: Tumor Microenvironment (TME) provides the essential prerequisite niche for promoting cancer progression and metastasis. Calebin A, a component of Curcuma longa, has long been investigated as a safe multi-targeted agent with anti-tumor and anti-inflammatory properties. However, the multicellular-TME-induced malignancy and the anti-tumorigenic potential of Calebin A on colorectal cancer cells (CRC) in 3D-alginate cultures are not yet understood and more-in depth research is needed. Methods: 3D-alginate tumor cultures (HCT116 cells) in the multicellular pro-inflammatory TME (fibroblast cells/T-lymphocytes), TNF-β-TME (fibroblast cells/TNF-β) were treated with/without Calebin A to address the pleiotropic actions of Calebin A in the CRC. Results: We found that Calebin A down-modulated proliferation, vitality and migration of HCT116 cells in 3D-alginate cultures in multicellular pro-inflammatory TME or TNF-β-TME. Also, Calebin A suppressed TNF-β-, similar to multicellular-TME-induced phosphorylation of NF-kappaB in a concentration-dependent manner. NF-kappaB-promoting pro-inflammatory mediators, associated with tumor growth and anti-apoptotic molecules (i.e. MMP-13, Ki-67, β1-integrin, caspase-3) and its translocation to the nucleus in HCT116 cells were increased in both TME cultures. The multicellular-TME cultures further induced the survival of cancer stem cells (CSCs) (up-regulation of CD133, CD44, ALDH1). Last but not least, Calebin A suppressed multicellular-, similar to TNF-β-TME-induced rigorous up-regulation of NF-kappaB phosphorylation, various NF-kappaB-regulated gene products, CSCs activation and survival in 3D-alginate tumor cultures. Conclusions: The down-modulation of multicellular pro-inflammatory-, similar to TNF-β-TME-induced CRC proliferation, survival and migration by the multitargeting agent Calebin A could be a new therapeutic strategy to suppress inflammation and CRC tumorigenesis.